2020
DOI: 10.1111/famp.12592
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial Testing a Parenting Intervention Among Afghan and Rohingya Refugees in Malaysia

Abstract: Refugee families experience uncertainty and stress when residing in countries of first asylum, such as Malaysia, and may benefit from supportive parenting interventions. In the greater Kuala Lumpur, Malaysia area we piloted an eight‐week parenting program with 79 Rohingya and Afghan mothers in nine separate groups. Participants were randomized to an intervention group or a waitlist control group and those in each arm completed a 3‐month follow‐up assessment. Program content addressed positive discipline, stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Looking at the studies with large effect size estimates (SMD ≥ .80) in adult samples, six studies emerged (Ali, 2020;De Graaff et al, 2020;Koch et al, 2020;Orang et al, 2022;Renner et al, 2011;Shaw et al, 2021). In a study with moderate risk of bias, De Graaff et al ( 2020 (2020) found constantly larger effect sizes for the same program in a population of adult Syrian refugees in the Netherlands, Spaaij ( 2022) -yet in a feasibility and acceptability trial -reported nonsignificant but inverse effect sizes for a sample of Syrian refugees and asylum seekers in Switzerland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking at the studies with large effect size estimates (SMD ≥ .80) in adult samples, six studies emerged (Ali, 2020;De Graaff et al, 2020;Koch et al, 2020;Orang et al, 2022;Renner et al, 2011;Shaw et al, 2021). In a study with moderate risk of bias, De Graaff et al ( 2020 (2020) found constantly larger effect sizes for the same program in a population of adult Syrian refugees in the Netherlands, Spaaij ( 2022) -yet in a feasibility and acceptability trial -reported nonsignificant but inverse effect sizes for a sample of Syrian refugees and asylum seekers in Switzerland.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the remaining four studies with large effect sizes in adult samples was associated with at least 'some concerns' for risk of bias in three out of five domains (Ali, 2020;Orang et al, 2022;Renner et al, 2011;Shaw et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Morina et al ( 2018 ) used mastery experiences to strengthen self‐efficacy among a Turkish sample of refugees resettled in Switzerland. In addition, parenting interventions aimed at supporting refugee parents seem to contribute to strengthening parental self‐efficacy in Syrian, Karen, Rohingya, and Afghan refugee families (El‐Khani et al, 2018 ; Hoffman et al, 2020 ; Shaw et al, 2020 ). Until now, however, studies primarily focused on the feasibility and acceptability of programs in those populations, and the field is less developed in terms of the specific effects that these programs yield.…”
Section: Can We Promote Parental Self‐efficacy? Evidence For Malleabi...mentioning
confidence: 99%
“…For example, qualitative work with Afghani women who settled in Australia found that many faced violence, exclusion, and discrimination from other refugee groups and native peoples during their time in refugee camps in Pakistan (Kavian et al, 2020). Additionally, many Rohingya refugee families have made Bangladesh or Malaysia their country of "first asylum," but may continue on to other countries or return to Myanmar when it is safe to do so (Shaw et al, 2020). Importantly, wealthier migrants may be able to travel by air rather than embark on land or sea journeys, whereas migrants from lower socioeconomic brackets may not have this option.…”
Section: Context Of Transitmentioning
confidence: 99%